Increasing Efficiency of Vent Brick Arabian Style Manufacturing Case Study: Muslim Modern at Pattani Province - Sani, Suhaidee; Rawangwong, Surasit; Rojananukul, Julaluk; Meengam, Chaiyoot (RMUTP Research Journal Sciences and Technology, 2022)
The objective of this study is to improve the efficiency in manufacturing process of Arabian-style ventilation bricks with a new production method that uses a machine. The study focuses on all steps of productions in order to increase productivity. After the experiment, the study shows that the improvement of ventilation brick manufacturing includes the increase in production volume from 20 pieces per day to 50 pieces per day, representing an increase of 76.19 percent; and the decrease in production cycle time originally from 1,401 minutes per piece to 97 minutes per piece, representing a decrease of 93.07 percent respectively.